Water-based scratch-resistant acrylic amino aluminum powder stoving varnish and preparation method thereof

By using graphene oxide composite materials and spherical silicon carbide nanoparticles in modified epoxy resin in water-based scratch-resistant acrylic aluminium powder paint, the problems of contamination and poor performance of traditional aluminum powder paint are solved, and efficient Resistant to scratches, wear and corrosion.

CN119192930AInactive Publication Date: 2024-12-27SHANDONG ZHONGSHENG PAINT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411714464.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Solvent-based coatings of traditional aluminum powder paints pollute the environment and their performance is difficult to balance in terms of flexibility and hardness. Conventional water-based metal paints are harsh in baking temperature and time, and have insufficient scratch resistance.

Method used

Using water-based scratch-resistant acrylic aluminium powder paint, the graphene oxide composite material and spherical silicon carbide nanoparticles in the epoxy resin form rolling friction and self-lubricating effects, combined with a high-density crosslinking network, enhance interface bonding and Barrier performance.

Benefits of technology

It improves the scratch, wear and corrosion resistance of the coating, reduces friction damage and permeability, and optimizes the mechanical stability and corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a water-based scratch-resistant acrylic amino aluminum powder stoving varnish and a preparation method thereof, and relates to the technical field of paints.The water-based scratch-resistant acrylic amino aluminum powder stoving varnish is prepared from, by weight, water-based acrylic resin, modified epoxy resin, amino resin, water-based aluminum powder, a water-based defoaming agent, deionized water and a film-forming cosolvent, a mixed solution is prepared, then an amine neutralizer is added while stirring is conducted, and the water-based scratch-resistant acrylic amino aluminum powder stoving varnish is obtained. And adjusting the pH value of the mixed solution to obtain the water-based scratch-resistant acrylic amino aluminum powder stoving varnish. The modified epoxy resin is obtained by modifying graphene oxide loaded with nano silicon carbide by utilizing co-crosslinking between polydopamine and polyethyleneimine and filling epoxy resin with the graphene oxide loaded with nano silicon carbide; the graphene oxide composite material has the advantages of excellent wear resistance, scratch resistance and corrosion resistance due to the various functions of the graphene oxide composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a water-based scratch-resistant acrylic amino aluminum powder baking varnish and a preparation method thereof. Background Art

[0002] Paint is applied to the surface of the object to be protected or decorated, and can form a continuous solid film that is firmly attached to the object to be coated. It is also called paint film or coating. It is usually a viscous liquid made of resin, oil, or emulsion, with or without pigments, fillers, and corresponding additives, and is prepared with organic solvents or water. Traditional aluminum paint coating is generally based on solvent-based paint. The paint used to produce aluminum paint is usually composed of alkyd resin, solvent and aluminum powder slurry. Alkyd resin is produced by esterification reaction of polyacids, monobasic acids and polyols in a resin reactor. The solvent used will be discharged into the atmosphere, which not only wastes resources, but also pollutes the environment and causes certain harm to the human body.

[0003] In recent years, with the increasing awareness of environmental protection in the whole society, the industry has gradually shown the above trend of attention to baking paint, and the most commonly used is metal baking paint. However, conventional water-based metal baking paint has strict requirements on baking temperature and baking time in order to achieve good performance, and it is difficult to balance flexibility and hardness. If the hardness is high, the flexibility is poor and it is not impact-resistant; if the flexibility is good, the hardness is reduced, the cross-linking density is reduced, resulting in reduced adhesion, salt spray resistance and chemical resistance. Summary of the invention

[0004] The object of the present invention is to provide a water-based scratch-resistant acrylic amino aluminum powder baking varnish and a preparation method thereof, so as to solve the problems raised in the background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: A water-based scratch-resistant acrylic amino aluminum powder baking varnish comprises the following components in parts by weight: 50-65 parts of water-based acrylic resin, 9-11 parts of modified epoxy resin, 19-21 parts of amino resin, 6-8 parts of water-based aluminum powder, 0.02-0.2 parts of water-based defoaming agent, 12-20 parts of deionized water, 1.3-2 parts of amine neutralizer and 5-7 parts of film-forming cosolvent.

[0006] The modified epoxy resin is obtained by utilizing co-crosslinking between polydopamine and polyethyleneimine to modify graphene oxide loaded with nano-silicon carbide and filling the graphene oxide into epoxy resin.

[0007] Furthermore, the preparation method of the modified epoxy resin is: S1. Add 3-glycidyloxypropyltrimethyloxysilane, acetic acid and nano-silicon carbide to ethanol, ultrasonicate the suspension for 1-1.5h, stir at 60-80°C for 3-5h, wash with ethanol and dry, then add 4g / L ethanol solution of graphene oxide, stir for 4-5h, centrifuge and dry to obtain graphene oxide loaded with silicon carbide; It should be noted that the silicon carbide nanoparticles modified by the silane coupling agent react with the hydroxyl functional groups on the graphene oxide and are then grafted into the lamellar structure of the graphene oxide.

[0008] S2, dissolving the silicon carbide-loaded graphene oxide, dopamine hydrochloride and polyethyleneimine in a trimethylaminomethane buffer solution with a molar concentration of 20 mM and a pH of 8.5, stirring the mixture at 400 r / min for 6-7 hours, washing the precipitate after centrifugation until the pH value of the upper solution becomes neutral, collecting the precipitate, and obtaining a graphene oxide composite material; It should be noted that the introduction of branched polyethyleneimine increases the number of amino active sites, quickly forms a cross-linked network with polydopamine, shortens the time of dopamine self-polymerization, destroys the formation of polydopamine oligomers, and obtains high cross-linking density amino branched polyethyleneimine and polydopamine-modified silicon carbide-loaded graphene oxide through Michael addition reaction and Schiff base reaction.

[0009] S3. Transfer the prepared graphene oxide composite material to acetone, ultrasonically treat for 10-15 minutes, then add epoxy resin, stir for 1-1.5 hours, add curing agent, stir for another 30-50 minutes, transfer the prepolymer to a vacuum drying oven at 40-60°C to obtain a modified epoxy resin.

[0010] Furthermore, in step S1, the dosage ratio of 3-glycidyloxypropyltrimethyloxysilane, acetic acid, nano-silicon carbide, ethanol and ethanol solution of graphene oxide is 0.5-1.5 mL: 0.5-1.5 mL: 0.5-1.5 g: 150-250 mL: 150-250 mL.

[0011] Furthermore, in the step S2, the mass concentration of the silicon carbide-loaded graphene oxide, dopamine hydrochloride and polyethyleneimine in the trimethylaminomethane buffer solution is 2 mg / mL.

[0012] Furthermore, in step S3, the usage ratio of the graphene oxide composite material, acetone, epoxy resin and curing agent is 10-20 mg: 3-8 mL: 5-15 g: 3-8 g.

[0013] Furthermore, in step S3, the curing agent is trimethylaminomethane.

[0014] Furthermore, the defoaming agent is polyether-modified silane.

[0015] Furthermore, the amine neutralizing agent is aqueous ammonia, N,N-dimethylethanolamine, triethylamine or triethanolamine.

[0016] Furthermore, the film-forming cosolvent is ethylene glycol butyl ether, propylene glycol methyl ether or diethylene glycol butyl ether.

[0017] The invention discloses a method for preparing a water-based scratch-resistant acrylic amino aluminum powder baking varnish. The method comprises the following steps: placing water-based acrylic resin, modified epoxy resin, amino resin, water-based aluminum powder, water-based defoamer, deionized water and film-forming auxiliary solvent into a high-speed disperser by weight, stirring the mixture at a speed of 800-1200 rpm for 8-15 minutes to prepare a mixed solution; then, adding a proper amount of an amine neutralizer while stirring, and adjusting the pH value of the mixed solution to 7.5-8 to obtain the water-based scratch-resistant acrylic amino aluminum powder baking varnish.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) When friction and scratches occur on the paint surface, the layered graphene oxide and spherical silicon carbide nanoparticles in the graphene oxide composite material in the matrix can form a rolling friction effect. In addition, as a self-lubricating material, the graphene oxide composite material forms a continuous and stable transfer film during the sliding process, producing a lubricating effect, reducing the friction damage caused by the matrix during the friction process, improving the material's load-bearing capacity and wear resistance, and enhancing the scratch resistance; (2) The amino groups in the graphene oxide composite material combine with the epoxy groups in the epoxy resin, allowing the graphene oxide composite material to be evenly dispersed in the matrix and tightly bound at the interface, thereby enhancing the interfacial bonding strength between the graphene oxide and the matrix, protecting the graphene oxide composite material from separation due to friction during the friction process, improving the mechanical stability of the coating, controlling the material's peeling phenomenon, reducing the material's friction damage, and improving the material's scratch resistance; (3) The high-density cross-linked network formed by polydopamine and polyethyleneimine and the lamellar structure of graphene oxide form a composite material that fills the pores generated during the resin curing process, plays a barrier role, reduces the permeability of the material, and improves the corrosion resistance of the material. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] The preparation method of the modified epoxy resin in the embodiment of the present invention is: S1. Add 1 mL of 3-glycidyloxypropyltrimethyloxysilane, 1 mL of acetic acid and 0.8 g of nano-silicon carbide to 200 mL of ethanol, ultrasonicate the suspension for 1 h, stir at 70 ° C for 4 h, wash with ethanol and dry, then add 200 mL of ethanol solution containing 0.8 g of graphene oxide, stir for 4 h, and centrifuge to obtain graphene oxide loaded with silicon carbide; S2, dissolving the silicon carbide-loaded graphene oxide, dopamine hydrochloride and polyethyleneimine in a trimethylaminomethane buffer solution with a molar concentration of 20 mM and a pH of 8.5, wherein the concentration of the buffer solution of the silicon carbide-loaded graphene oxide, dopamine hydrochloride and polyethyleneimine is 2 mg / mL; stirring the mixture at 400 r / min for 6 h, washing the precipitate after centrifugation until the pH value of the upper solution becomes neutral, collecting the precipitate, and obtaining a graphene oxide composite material; S3. Transfer 15 mg of the prepared graphene oxide composite material into 5 mL of acetone and ultrasonically treat for 10 min. Then, add 10 g of epoxy resin and stir for 1 h. Add 5.5 g of trimethylaminomethane and stir for another 30 min. Transfer the prepolymer to a vacuum drying oven at 50° C. to obtain a modified epoxy resin.

[0021] Embodiment 1: A method for preparing a water-based scratch-resistant acrylic amino aluminum powder paint. By weight, 50 parts of water-based acrylic resin, 10 parts of modified epoxy resin, 20 parts of amino resin, 6 parts of water-based aluminum powder, 0.05 parts of polyether modified silane, 15 parts of deionized water and 5 parts of ethylene glycol butyl ether are placed in a high-speed disperser and stirred at a speed of 800 rpm for 8 minutes to prepare a mixed solution; then, 1.5 parts of ammonia water is added while stirring, and the pH value of the mixed solution is adjusted to 7.5 to obtain a water-based scratch-resistant acrylic amino aluminum powder paint.

[0022] Example 2: A method for preparing a water-based scratch-resistant acrylic amino aluminum powder paint. By weight, 52 parts of water-based acrylic resin, 9 parts of modified epoxy resin, 19 parts of amino resin, 7 parts of water-based aluminum powder, 0.08 parts of polyether-modified silane, 18 parts of deionized water and 6 parts of propylene glycol methyl ether are placed in a high-speed disperser and stirred at a speed of 1000 rpm for 10 minutes to prepare a mixed solution; then, 1.8 parts of N,N-dimethylethanolamine are added while stirring, and the pH value of the mixed solution is adjusted to 7.8 to obtain a water-based scratch-resistant acrylic amino aluminum powder paint.

[0023] Example 3: A method for preparing a water-based scratch-resistant acrylic amino aluminum powder paint. By weight, 54 parts of water-based acrylic resin, 10 parts of modified epoxy resin, 20 parts of amino resin, 8 parts of water-based aluminum powder, 0.1 parts of polyether-modified silane, 20 parts of deionized water and 7 parts of diethylene glycol butyl ether are placed in a high-speed disperser and stirred at a speed of 1200 rpm for 15 minutes to prepare a mixed solution; then, 2.0 parts of triethylamine are added while stirring, and the pH value of the mixed solution is adjusted to 8.0 to obtain a water-based scratch-resistant acrylic amino aluminum powder paint.

[0024] Example 4: A method for preparing a water-based scratch-resistant acrylic amino aluminum powder paint. By weight, 60 parts of water-based acrylic resin, 11 parts of modified epoxy resin, 21 parts of amino resin, 8 parts of water-based aluminum powder, 0.2 parts of polyether modified silane, 20 parts of deionized water and 7 parts of ethylene glycol butyl ether are placed in a high-speed disperser and stirred at a speed of 1000 rpm for 10 minutes to prepare a mixed solution; then, 2.0 parts of triethanolamine are added while stirring, and the pH value of the mixed solution is adjusted to 7.5 to obtain a water-based scratch-resistant acrylic amino aluminum powder paint.

[0025] Comparative Example 1: The preparation method of the modified epoxy resin in this comparative example is: S1. Add 1 mL of 3-glycidyloxypropyltrimethyloxysilane, 1 mL of acetic acid and 0.8 g of nano-silicon carbide to 200 mL of ethanol, ultrasonicate the suspension for 1 h, stir at 70 ° C for 4 h, wash with ethanol and dry, then add 200 mL of ethanol solution containing 0.8 g of graphene oxide, stir for 4 h, and centrifuge to obtain graphene oxide loaded with silicon carbide; S2. Transfer 15 mg of the prepared silicon carbide-loaded graphene oxide into 5 mL of acetone and ultrasonically treat for 10 min. Then, add 10 g of epoxy resin and stir for 1 h. Add 5.5 g of trimethylaminomethane and stir for another 30 min. Transfer the prepolymer to a vacuum drying oven at 50° C. to obtain a modified epoxy resin.

[0026] A method for preparing a water-based scratch-resistant acrylic amino aluminum powder baking varnish comprises the following steps: placing 50 parts of water-based acrylic resin, 10 parts of modified epoxy resin, 20 parts of amino resin, 6 parts of water-based aluminum powder, 0.05 parts of polyether-modified silane, 15 parts of deionized water and 5 parts of ethylene glycol butyl ether into a high-speed disperser by weight, stirring the mixture at a speed of 800 rpm for 8 minutes to prepare a mixed solution; then, adding 1.5 parts of ammonia water while stirring, and adjusting the pH value of the mixed solution to 7.5 to obtain the water-based scratch-resistant acrylic amino aluminum powder baking varnish.

[0027] Comparative Example 2: The preparation method of the modified epoxy resin in this comparative example is: S1. Dissolve graphene oxide, dopamine hydrochloride and polyethyleneimine in a trimethylaminomethane buffer solution with a molar concentration of 20 mM and a pH of 8.5, wherein the concentration of the buffer solution of graphene oxide, dopamine hydrochloride and polyethyleneimine loaded with silicon carbide is 2 mg / mL; stir the mixture at 400 r / min for 6 h, wash the precipitate after centrifugation until the pH value of the upper solution becomes neutral, collect the precipitate, and obtain a graphene oxide composite material; S2. Transfer 15 mg of the prepared graphene oxide composite material into 5 mL of acetone and ultrasonically treat for 10 min. Then, add 10 g of epoxy resin and stir for 1 h. Add 5.5 g of trimethylaminomethane and stir for another 30 min. Transfer the prepolymer to a vacuum drying oven at 50° C. to obtain a modified epoxy resin.

[0028] A method for preparing a water-based scratch-resistant acrylic amino aluminum powder baking varnish comprises the following steps: placing 50 parts of water-based acrylic resin, 10 parts of modified epoxy resin, 20 parts of amino resin, 6 parts of water-based aluminum powder, 0.05 parts of polyether-modified silane, 15 parts of deionized water and 5 parts of ethylene glycol butyl ether into a high-speed disperser by weight, stirring the mixture at a speed of 800 rpm for 8 minutes to prepare a mixed solution; then, adding 1.5 parts of ammonia water while stirring, and adjusting the pH value of the mixed solution to 7.5 to obtain the water-based scratch-resistant acrylic amino aluminum powder baking varnish.

[0029] Comparative Example 3: The preparation method of the modified epoxy resin in this comparative example is: 15 mg of graphene oxide was transferred to 5 mL of acetone and ultrasonically treated for 10 min. Subsequently, 10 g of epoxy resin was added and stirred for 1 h. 5.5 g of trimethylaminomethane was added and stirred for another 30 min. The prepolymer was transferred to a vacuum drying oven at 50 °C to obtain a modified epoxy resin.

[0030] A method for preparing a water-based scratch-resistant acrylic amino aluminum powder baking varnish comprises the following steps: placing 50 parts of water-based acrylic resin, 10 parts of modified epoxy resin, 20 parts of amino resin, 6 parts of water-based aluminum powder, 0.05 parts of polyether-modified silane, 15 parts of deionized water and 5 parts of ethylene glycol butyl ether into a high-speed disperser by weight, stirring the mixture at a speed of 800 rpm for 8 minutes to prepare a mixed solution; then, adding 1.5 parts of ammonia water while stirring, and adjusting the pH value of the mixed solution to 7.5 to obtain the water-based scratch-resistant acrylic amino aluminum powder baking varnish.

[0031] The obtained samples were sprayed on the surface of Q235 low carbon steel, and ultrasonically cleaned with anhydrous ethanol after sandblasting. All samples were cured at room temperature for 48 hours. The thickness of the composite coating sprayed on the steel plate was 90±5µm. The wear resistance of these samples was tested. The performance was tested by a friction and wear tester with a vertical load of 30N, a back and forth friction speed of 83.3mm / s, a wear time of 5min, a friction ball of zirconia ball, and a stroke of 10mm. The wear resistance was then calculated in the form of mass loss. The anti-corrosion performance of the composite material was tested on an electrochemical workstation. The anti-corrosion performance of the composite material in 3.5% NaCl aqueous solution was studied by open circuit potential (OCP) and electrochemical impedance spectroscopy (EIS). The electrochemical measurement was performed using a conventional three-electrode system, and the experimental data were fitted using ZsimDemo software. The experimental results are shown in Table 1.

[0032] .

[0033] According to the analysis of experimental data, the spherical silicon carbide nanoparticles in the embodiment are distributed between the layers and on the surface of the graphene oxide sheet. When friction and scratches occur on the surface of the material, a rolling friction will be formed to reduce the friction coefficient. In addition, graphene oxide is a self-lubricating material that can form a continuous transfer film during the friction process to reduce the damage caused by friction and scratches. In addition, the tightly cross-linked network of polyethyleneimine and polydopamine not only firmly fixes the graphene oxide loaded with silicon carbide in the matrix, reducing the friction loss of the material, but also improves the barrier property. The various functions of the graphene composite material make the material have excellent wear resistance, scratch resistance and corrosion resistance; in the comparative examples, the material of comparative example 1 may slip and peel off when rubbed and scratched, increasing the wear of the material; the material of comparative example 2 undergoes adhesive wear and fatigue wear when rubbed and scratched, and the friction coefficient and damage are relatively large; the material of comparative example 2 has poor wear resistance, scratch resistance and corrosion resistance when rubbed and scratched, because graphene oxide is prone to aggregation when added alone, resulting in uneven distribution, which reduces the overall performance of the material.

[0034] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A water-based scratch-resistant acrylic amino aluminum powder baking varnish, characterized in that: The invention comprises the following components in parts by weight: 50-65 parts of water-based acrylic resin, 9-11 parts of modified epoxy resin, 19-21 parts of amino resin, 6-8 parts of water-based aluminum powder, 0.02-0.2 parts of water-based defoaming agent, 12-20 parts of deionized water, 1.3-2 parts of amine neutralizer and 5-7 parts of film-forming cosolvent; The modified epoxy resin is obtained by utilizing co-crosslinking between polydopamine and polyethyleneimine to modify graphene oxide loaded with nano-silicon carbide and filling the graphene oxide into epoxy resin.

2. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 1, characterized in that: The preparation method of the modified epoxy resin is: S1. Add 3-glycidyloxypropyltrimethyloxysilane, acetic acid and nano-silicon carbide to ethanol, ultrasonicate the suspension for 1-1.5h, stir at 60-80°C for 3-5h, wash with ethanol and dry, then add 4g / L ethanol solution of graphene oxide, stir for 4-5h, centrifuge and dry to obtain graphene oxide loaded with silicon carbide; S2, dissolving the silicon carbide-loaded graphene oxide, dopamine hydrochloride and polyethyleneimine in a trimethylaminomethane buffer solution with a molar concentration of 20 mM and a pH of 8.5, stirring the mixture at 400 r / min for 6-7 hours, washing the precipitate after centrifugation until the pH value of the upper solution becomes neutral, collecting the precipitate, and obtaining a graphene oxide composite material; S3. Transfer the prepared graphene oxide composite material to acetone, ultrasonically treat for 10-15 minutes, then add epoxy resin, stir for 1-1.5 hours, add curing agent, stir for another 30-50 minutes, transfer the prepolymer to a vacuum drying oven at 40-60°C to obtain a modified epoxy resin.

3. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 2, characterized in that: In the step S1, the dosage ratio of 3-glycidyloxypropyltrimethyloxysilane, acetic acid, nano-silicon carbide, ethanol and ethanol solution of graphene oxide is 0.5-1.5 mL: 0.5-1.5 mL: 0.5-1.5 g: 150-250 mL: 150-250 mL.

4. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 2, characterized in that: In the step S2, the mass concentration of the silicon carbide-loaded graphene oxide, dopamine hydrochloride and polyethyleneimine in the trimethylaminomethane buffer solution is 2 mg / mL.

5. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 2, characterized in that: In the step S3, the amount ratio of the graphene oxide composite material, acetone, epoxy resin and curing agent is 10-20 mg: 3-8 mL: 5-15 g: 3-8 g.

6. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 2, characterized in that: In step S3, the curing agent is trimethylaminomethane.

7. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 1, characterized in that: The defoamer is polyether modified silane.

8. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 1, characterized in that: The amine neutralizing agent is ammonia water, N,N-dimethylethanolamine, triethylamine or triethanolamine.

9. The water-based scratch-resistant acrylic amino aluminum powder baking varnish according to claim 1, characterized in that: The film-forming auxiliary solvent is ethylene glycol butyl ether, propylene glycol methyl ether or diethylene glycol butyl ether.

10. The method for preparing a water-based scratch-resistant acrylic amino aluminum powder baking varnish according to any one of claims 1 to 9, characterized in that: The aqueous acrylic resin, modified epoxy resin, amino resin, aqueous aluminum powder, aqueous defoamer, deionized water and film-forming cosolvent are placed in a high-speed disperser according to weight proportions, and stirred at a speed of 800-1200 rpm for 8-15 minutes to prepare a mixed solution; then, an amine neutralizer is added while stirring, and the pH value of the mixed solution is adjusted to 7.5-8 to obtain an aqueous anti-scratch acrylic amino aluminum powder baking paint.

Citation Information

Patent Citations

  • Water-based aluminum powder baking varnish and preparation method

    CN112375443A